Framing Analysis of News Coverage on the BBM Price Increase in Online Media - Reza, Faisal; Hanafi; Azahar, Yudi Kurnia (Yayasan Sinergi Kawula Muda, 2023)
This study examines the framing of news coverage related to the increase in fuel prices (BBM) on two prominent Indonesian online media platforms, Kumparan.com and Kompas.com, during the period of September 3–7, 2022. Utilizing Robert N. Entman’s framing analysis model, the research explores how these media outlets construct and present the issue of the BBM price hike through the four elements of framing: defining problems, diagnosing causes, making moral judgments, and offering treatment recommendations. The research adopts a qualitative content analysis approach, systematically analyzing articles from both platforms to identify recurring themes and framing techniques. The study employs a purposive sampling method to select relevant news articles, ensuring that the content analyzed is directly related to the BBM price hike during the specified period. The findings reveal significant differences in how each media platform frames the issue. Kumparan.com primarily views the government’s decision to raise BBM prices as a source of public discontent, highlighting the negative impact on various societal groups and attributing the problem largely to government actions. In contrast, Kompas.com adopts a more balanced approach, acknowledging both the necessity of the government’s decision in light of rising global oil prices and the public's grievances. This platform frames the policy as a difficult but necessary step to maintain economic stability. The study concludes that media framing plays a crucial role in shaping public perception, with each outlet presenting the same event in ways that reflect their editorial stances and underlying ideologies. The research suggests that future studies could benefit from incorporating constructionist theories and critical discourse analysis to further understand the mechanisms of media framing and its impact on public discourse.